2021
DOI: 10.1126/scitranslmed.abb3735
|View full text |Cite
|
Sign up to set email alerts
|

The intratumoral CXCR3 chemokine system is predictive of chemotherapy response in human bladder cancer

Abstract: Chemotherapy has direct toxic effects on cancer cells; however, long-term cancer control and complete remission are likely to involve CD8+ T cell immune responses. To study the role of CD8+ T cell infiltration in the success of chemotherapy, we examined patients with muscle invasive bladder cancer (MIBC) who were categorized on the basis of the response to neoadjuvant chemotherapy (NAC). We identified the intratumoral CXCR3 chemokine system (ligands and receptor splice variants) as a critical component for tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 87 publications
2
31
0
Order By: Relevance
“…C-X-C motif chemokine 11 (CXCL11) has been reported to contribute to the progression of tumors. In our study, we demonstrated that the expression of CXCL11 was negatively correlated with prognosis of BUC, which was consistent with the result of Vollmer Tino et al In addition, they also found that the expression of CXCL11 was predictive of chemotherapy response in human bladder cancer (27). We also demonstrated the correlation between CXCL11 and chemotherapy drugs in this study, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…C-X-C motif chemokine 11 (CXCL11) has been reported to contribute to the progression of tumors. In our study, we demonstrated that the expression of CXCL11 was negatively correlated with prognosis of BUC, which was consistent with the result of Vollmer Tino et al In addition, they also found that the expression of CXCL11 was predictive of chemotherapy response in human bladder cancer (27). We also demonstrated the correlation between CXCL11 and chemotherapy drugs in this study, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The current study, based on IHC analysis, revealed that CD3 + T cells (CD4 + and CD8 + T cells) were depleted in SIV-infected macaque brains in the first week of infection, but were replaced by the second week after infection. This homing of CD3 + T cells to the brain during the second week may occur at the CXCR3-CXCL10/CXCL11 axis, as evident from the several-fold upregulation of their corresponding gene signatures only during the second week (30,31). Again, to our surprise, the aforementioned T cell dynamics were uniform among all 3 brain regions, supporting the hypothesis that this response could have been induced by peripheral factors.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, the infiltration had only replaced the initial loss of cells to the level of the uninfected control. But a higher number of CD8 + T cells among the total number of infiltrated T cells during the second week after infection in conjunction with upregulation of granzyme A and B transcripts -potentially also reflecting NK cell activation -suggest the cytotoxic nature of this response (31). These hypotheses require further validation.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, CXCR3 ligands could directly induce activation of stem-like CD8 + T cells, as suggested by a recent study of muscle-invasive bladder cancers where these cells acquired effector-like properties upon treatment with CXCL11. 53 Although our results suggest that TCT primarily mobilizes T cells from immune niches outside the tumor, the contribution of TILs residing within the tumor before TCT cannot be disregarded. For example, Miller et al showed that small populations of stem-like PD-1 lo Tim-3 − TCF-1 + CD8 + T cells naturally reside within the parenchyma of B16 and D4M.3A murine melanoma tumors and display effector cytokine polyfunctionality, divide more extensively, and give rise to the terminally differentiated CD8 + T cell pool.…”
Section: Discussionmentioning
confidence: 65%
“…Finally, CXCR3 ligands could directly induce activation of stem-like CD8 + T cells, as suggested by a recent study of muscle-invasive bladder cancers where these cells acquired effector-like properties upon treatment with CXCL11. 53 …”
Section: Discussionmentioning
confidence: 99%